Leaving Military Service with a Military Body: Insights for Pastoral Care and Counseling. (June 2019) - Grimell, Jan
The significance of the body has emerged as a vital yet neglected element in the transition from military to civilian life. The recognition of a military body enhances the understanding of potential pastoral and counseling needs among veterans beyond the mind and the soul. This article attempts to contribute to further knowledge about this topic, drawing from both theory and empirical research, in an effort to provide insights for pastoral care and counseling.